2020
DOI: 10.48550/arxiv.2011.14422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fixing Left and Right: Assignment of Chiral Elemental Crystal Structures using Kikuchi Diffraction

Abstract: Crystals of the chemical elements manganese, tellurium, and selenium can show the effects of handedness. For crystallographic materials analysis, this implies that the presence of two, physically different, enantiomorphic, variants of these elemental crystal structures needs to be taken into account, because of the possible effects of a changing sense of chirality on the properties of the material. Due to fundamental limitations of kinematical X-ray scattering in crystals, however, the effects of chirality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…A combination of x-ray diffraction and EBSD analysis previously introduced for the chiral CoSi phase ( 16) is applied to investigate polycrystalline materials of Pt 2 Cu 3 B and -Mn. Preliminary EBSD studies on -Mn are reported in (27). First, we present the analyses of the phase Pt 2 Cu 3 B, where the assignment of the enantiomorphs by the Kikuchi pattern analysis is proven by x-ray single-crystal diffraction experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of x-ray diffraction and EBSD analysis previously introduced for the chiral CoSi phase ( 16) is applied to investigate polycrystalline materials of Pt 2 Cu 3 B and -Mn. Preliminary EBSD studies on -Mn are reported in (27). First, we present the analyses of the phase Pt 2 Cu 3 B, where the assignment of the enantiomorphs by the Kikuchi pattern analysis is proven by x-ray single-crystal diffraction experiments.…”
Section: Introductionmentioning
confidence: 99%
“…However, single-crystal x-ray diffraction patterns remain essentially indistinguishable for enantiomorphs of chiral structures which contain only scattering ions of the same type, even when anomalous dispersion effects are taken into account. Higher-order harmonic generation and Kikuchi diffraction in electron scattering have recently been added to the list of techniques for the determination of chiral structures [8,9]. Likewise, resonant x-ray Bragg diffraction is a proven technique by which to label chiral structures, and it is the central topic of the present study [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies of the electronic properties of chiral structures [20][21][22][23][24] include β-Mn-type materials, e.g., Co-Zn-Mn alloys [25][26][27][28]. Yet, little attention has been given to structural chirality of the cubic form that we address [9]. The range of challenging properties found in chiral structures is wide, e.g., skyrmions [20,26], current induced magnetization [21], gyrotropic effects [22], and topological conduction [24].…”
Section: Introductionmentioning
confidence: 99%